Implicaciones de fusarium spp., en la etiología de la pudrición del fuste de gmelina arborea Roxb (melina) en el trópico húmedo Ecuatoriano. - Morán Vásquez, María Estefanía (2020)
The present study was carried out in Gmelina arborea Roxb (melina) plantations of different ages (4,5; 2,3 and 2 years), belonging to the Santo Domingo de los Colorados and Buena Fé cantons, where three plots of 500 m